A comprehensive earthquake catalogue for Nepal and its adjoining region (Journal of Nepal Geological Society, 2018)
We have prepared a comprehensive earthquake catalogue for Nepal and its adjoining region. The catalogue contains magnitude - homogenized independent earthquakes of magnitude (Mw) between 4.0 and 8.5, which occurred between 1100 AD and 2018 AD. The catalogue contains date, time, latitude, longitude, depth, and magnitude of earthquakes, which are required in the study of seismic activity, tectonics and seismic hazard. Primary earthquake catalogues were collected from the International Seismological Centre (ISC, 2015), United States Geological Survey (USGS), which contain instrumentally recorded earthquake data and date back to 1900 AD. These primary catalogues of instrumentally recorded earthquakes were supplemented by historical earthquakes reported in published literatures, which occurred before 1900 AD. The collected primary catalogues were compiled and processed to develop a comprehensive catalogue. The developed comprehensive catalogue is expected to serve as a basic database for the study of seismic activity and seismic hazard in Nepal and its adjacent area.